Biography of prof. Andrzej Szczeklik. A bioethical perspective - Bołoz, Wojciech (Studia Ecologiae et Bioethicae, 2012)
Prof. Szczeklik has published more than 600 works and for the last decade, he has been the most frequently cited author in Polish scientific literature on the subjects of medicine and biology. His works also include three excellent interdisciplinary books that show the personality of the scientist, a system of thought, ideological affiliation, source of strength, and motivation. These are Catharsis. The healing power of Nature and Art (2007); Kore. The sick, sickness and the search for the medicine of the soul (2007) and thirdly, the posthumously published Immortality. Promethean sleep medicine (2012), all published by the Krakow printing house Znak. The author does engage in systematic exposition, rather the works take the form of an almanac. The professor talks about his research and treatment of patients, shows the di&culties encountered and emerging concerns, and even includes anecdotes of his family life. These books are written in lively, beautiful Polish.